Microstructure and Properties of Sulfoaluminate Cement-Based Grouting Materials: Effect of Calcium Sulfate Variety - Jianwu Zhang; Xuemao Guan; Xiao Wang; Xianwei Ma; Zhixin Li; Zhuoyue Xu; Biao Jin (Advances in Materials Science and Engineering)
Effect of calcium sulfate variety on the microstructure and properties of cement-based grouting materials made by sulfoaluminate cement clinker, calcium sulfate resource, and quicklime was investigated in this paper. Isothermal calorimetric, XRD, DTA-TG, and SEM-EDS were used to characterize the reaction process of cement-based grouting materials. The mechanical property and expansion of the harden body were also tested. The results showed that (1) the formation of ettringite can be completed during the first 2 h when gypsum was selected, causing nonexpansion of the harden body, and ettringite tends to be precipitated near the clinker grain, which has a negative influence on the “skeleton effect” of ettringite, resulting in lower strength of the hardened body. (2) Ettringite can be continually and slowly precipitated when an anhydride was chosen, and the hardened body shows significant expansion characteristic. Besides, ettringite in anhydride paste tends to be precipitated in the form of complex interleaving, which can generate a positive influence on mechanical property of the hardened paste.